Wpływ reklamy na zachowanie konsumenta w zakresie zakupu niektórych produktów spożywczych - Świątkowska, Monika (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 1998)
In this paper the results of the most successful advertisement campaigns for food products in the last years and the evaluation of their effectiveness was presented. The campaigns concerning chocolate, Pepsi Max drink, Łaciate milk and fats were analyzed. The effects of the 1996 so called butter versus margarine war campaign were presented together with the results of studies concerning consumer attitudes towards TV advertisment for margarine and the evaluation of their influence. An attempt to assess the attitude of Poles towards food advertisment was also made.